In-vivo loss of carbapenem resistance by extensively drug-resistant Klebsiella pneumoniae during treatment via porin expression modification - Suzanne Bialek-Davenet (Nature Portfolio, 2017)
Abstract Klebsiella pneumoniae, an Enterobacteriaceae that mostly causes hospital-acquired infections, belongs to the recently published WHO’s list of antibiotic-resistant pathogens that pose the greatest threat to human health. Indeed, K. pneumoniae is the enterobacterial species most concerned by both resistance to extended-spectrum cephalosporins, due to extended-spectrum β-lactamase (ESBL) production, and resistance to carbapenems, i.e. the β-lactams with the broadest activity. Carbapenem resistance is related not only to carbapenemase production, but also the production of ESBL or AmpC and the loss of general porins. Here, we characterized the mechanisms that deprived a urinary ESBL-producing, porin-deficient K. pneumoniae isolate, isolated 13 days after the end of a 40-day course of imipenem treatment, of its carbapenem resistance. These mechanisms were observed in two in-vivo derivatives of this isolate and consisted of mutations in genes encoding molecules that participate in the downregulation of the synthesis of PhoE, a porin specialized in phosphate transport. We obtained three new derivatives from one of the two original derivatives, following in-vitro antibiotic pressure, in which the carbapenem resistance was restored because of mutations in genes encoding molecules that participate in the upregulation of PhoE synthesis. Thus, we uncovered novel mechanisms of carbapenem resistance/susceptibility switching in K. pneumoniae.